Mental Health Consequences of Working from Home during the Pandemic - Jun Hyung Kim; Yu Kyung Koh; Jinseong Park (Global Labor Organization (GLO), 2022)
This paper examines the effects of working from home on mental health, with particular attention to the role of home environments. Using unique real time survey data from South Korea collected during the COVID-19 pandemic, we find that working from home negatively affects the mental health of workers, with greater effects on women and those who are primarily responsible for housework while also maintaining market work. Surprisingly, workers who live with children in the household do not suffer from the negative effects of working from home. Our findings suggest that family-work interaction may be an important factor in the optimal design of working from home.
Keywords: D13; L23; L84; M11; M54; 330; Working from home; home working; remote work; COVID-19; mental health; subjective well-being